(untitled) (Research, Society and Development, 2021)
Objective: To identify scientific production on the theme of patient advocacy by nurses in the context of intensive care between the years 2010 to 2020. Methods: Integrative literature review on the subject of patient advocacy in an intensive care unit (ICU) between the years 2010 to 2020, carried out in the databases: Publisher Medline (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS), Cochrane Library and Web of Science, and also in the electronic library Scientific Electronic Library Online (SCIELO). electronic library, 217 references were found, of which, 18 met the inclusion and exclusion criteria of the research. Result: The 18 selected articles were categorized according to the themes identified with the greatest recurrence, which consist of: nurse as a defender of the patient and family, barriers for the defense of the patient and nurse as an articulator between team, patient and family. Conclusion: This review makes it possible to take to the scientific community, what has been studied about the advocacy of patients in the ICU for the past 10 years, both nationally and internationally, in addition to highlighting the importance of nurses as defenders of the rights of the patient and the family, explain the existing barriers for the patient advocacy by the intensive care nurse to occur in a qualified way, and also demonstrates how the nurse performs the role of intermediary between his patient, family and multiprofessional team.